Menstrual cycle and perceived stress predict performance on the mnemonic similarity task. - Mateja Perović; Michael L Mack (PLoS ONE)
A growing body of literature demonstrates strong effects of ovarian hormones on the hippocampus and adjacent structures. However, resulting impacts on human cognition remain unclear. Addressing this gap, we examine pattern separation ability, a core hippocampal process, across the menstrual cycle using the mnemonic similarity task as a behavioral index (N = 183). We find a non-linear effect of the menstrual cycle, with pattern separation performance peaking in the high-estradiol, late follicular phase and reaching its lowest point during the mid-luteal phase, which is characterized by moderate estradiol and high progesterone levels. Additionally, we find that perceived stress may facilitate pattern separation performance. These results point to the importance of ovarian hormones for human cognition, reveal novel effects of perceived stress on mnemonic similarity task performance, and provide preliminary evidence of possible effects of menstrual cycle phase on neural pathways involved in pattern separation.